Case report: A rare case of cerebral herniation during glioma resection in a syphilis-positive patient - Wang, Han; Lin, Qianli; Wang, Fang; Yi, Yong; Xu, Xiaoping; Jiang, Jingcheng; Deng, Qingshan (Frontiers in Neurology, 2023)
Acute intraoperative cerebral herniation is catastrophic in craniotomy and seriously affects the outcomes of surgery and the prognosis of the patient. Although the probability of its occurrence is low, it can lead to severe disability and high mortality. We describe a rare case of intraoperative cerebral herniation that occurred in a syphilis-positive patient. The patient was diagnosed with both glioma and syphilis. When the glioma was completely removed under the surgical microscope, acute cerebral herniation occurred. An urgent intervention in cerebral herniation identified a collection of colorless, transparent, and protein-rich gelatinous substances rather than a hematoma, which is a more commonly reported cause of intraoperative cerebral herniation in the literature. We have found no previous descriptions of such cerebral herniation during craniotomy in a patient with syphilis and glioma. We suspected that the occurrence of intraoperative cerebral hernia might be related to the patient’s infection with syphilis. We considered the likelihood of an intraoperative cerebral herniation to be elevated when a patient had a disease similar to syphilis that could cause increased vascular permeability.